PENDEKATAN MARKETING MIX PADA USAHATANI KOPI - maria nurani (BiSTeK Pertanian, 2020)
Coffee is a commodity with a very important role in the national economy. International Coffee Organization said that Indonesia is the sixth rank in the world's largest coffee consumption. The climate in Indonesia is suitable for commercializing coffee plants, but the ability of farmers in marketing strategy to is still low so, the income obtained by coffee farmers is not optimum. In Malang, there are four coffee producing regions, one of it is Batu City which produces Arabica coffee. Arabica coffee has a higher selling value than robusta coffee and liberika. Coffee farmers in Batu City are spread in five sub-districts. The number of samples used in this study are twelve coffee farmers because in Batu there are twelve coffee producers who cultivated, processed into coffee powder, and marketed their own coffee products to consumers with diverse income and varied strategy designs in marketing process. The determination of the sample in this study is non probabilily sampling with purposive sampling. To measure the marketing mix is used a Likert scale, while to measure the income of coffee farmers an open questionnaire is used that will be distributed to farmers. The method is used descriptive analysis to determine the marketing mix strategy used by farmers, cost and income analysis to determine farmers' income and multiple linear regression analysis to determine the effect of marketing mix strategies on the income of coffee farmers in Batu City. The results showed that the marketing strategy used by coffee farmers in Batu City are 7p marketing mix strategy including products, prices, places, promotions, people, physical evidence and processes. The average farmer income per one coffee tree is Rp. 412.500 with an average total cost of Rp. 127.824, the average income received by coffee farmers in Batu City per one coffee tree is Rp. 284.676. Variable marketing mix 7p has a simultaneous and partial effect on income.